Single crystalline Cu2ZnSnS4 nanosheet arrays for efficient photochemical hydrogen generation. Issue 4 (8th December 2014) - Li, Bo-Jun; Yin, Peng-Fei; Zhou, Yu-Zhu; Gao, Zhi-Ming; Ling, Tao; Du, Xi-Wen
Abstract : We present a scalable route for the preparation of single crystalline Cu2 ZnSnS4 nanosheet arrays on conductive glass substrate, and demonstrate this architecture as an effective photocathode for solar hydrogen production. Abstract : Cu2 ZnSnS4 (CZTS) is promising for application in photoelectrochemical (PEC) water splitting systems, owing to its high absorption coefficient, abundance, non-toxicity and direct band gap suitable for solar conversion. Here we present a scalable route for the preparation of single crystalline CZTS nanosheet arrays (NSAs) on a conductive glass substrate by using CuS nanosheets (NSs) as a sacrificial template. When employed as a photocathode for PEC solar hydrogen production, the CZTS NSAs yield a photocurrent density of −1.32 mA cm −2 at 0 V versus the reversible hydrogen electrode under illumination of AM 1.5. This is the highest value ever reported for a CZTS-based electrode without a co-catalyst and protective layer. The CZTS NSAs photocathode remains active after 3.5 h of testing and maintains 60% of its initial photocurrent. This work demonstrates the reality of using earth-abundant CZTS for efficient hydrogen production.